Visualizing and Validating Multilingual Thematic Structures in Knowledge Graphs - Stasiuk, Mykola; Pavlyshenko, Bohdan (Комп’ютерне моделювання та інформаційні технології, 2026)
This study presents an extended methodological framework for exploring and validating thematic structures within multilingual cybersecurity discourse. Building upon bilingual knowledge graphs that integrate entities and relations extracted from English and Ukrainian texts, the work introduces a structural validation and visualization layer based on Association Rule Mining and analytics based on graphs. The objective is to expose statistically meaningful relationships between thematic clusters and to visualize these dependencies in a transparent, interpretable manner.